Personality Change among Newlyweds: Patterns, Predictors, and Associations with Marital Satisfaction over Time - Lavner, Justin A. (Dev Psychol, 2017)
The early years of marriage are a time of significant personal and relational changes as partners adjust to their new roles, but the specific ways that spouses’ personalities may change in early marriage and how these changes are associated with spouses’ marital satisfaction trajectories have been overlooked. Using 3 waves of data collected over the first 18 months of marriage (N = 338 spouses, or 169 heterosexual newlywed marriages), we examined changes in spouses’ self-reported Big 5 personality traits over time and the association between initial levels and changes in personality and spouses’ concurrent marital satisfaction trajectories. Results indicated significant changes in personality over time, including declines in agreeableness for husbands and for wives, declines in extraversion for husbands, declines in openness and neuroticism for wives, and increases in conscientiousness for husbands. These results did not differ by spouses’ age, demographics, relationship length prior to marriage, cohabitation prior to marriage, initial marital satisfaction, or parenthood status. Initial levels of personality as well as changes in personality over time were associated with spouses’ marital satisfaction trajectories. Taken together, these findings indicate that newlywed spouses’ personalities undergo meaningful changes during the newlywed years and these changes are associated with changes in spouses’ marital satisfaction. Further research is needed to understand the processes underlying changes in personality early in marriage and to examine the mechanisms linking changes in personality and changes in marital satisfaction.